Porta dos fundos – uma análise sob a perspectiva de Austin, Searle e Grice - Vieira, Fernanda Miranda da Silva (2014)
Motivated by the interest in the subjects addressed in the field of Pragmatics, this research aims to analyze the genre sketching from the perspective of two models of pragmatic studies. For that, we chose to work with two versions of theories of speech acts and one with implicit meaning. For speech acts, we chose the Theory of Speech Acts proposed by Austin (1962) and the formulation of Searle's Indirect Acts (1979). For implicit meaning, we chose to work with the Conversational Implications of Grice (1975). Such a choice is justified by the importance these themes play within Pragmatics. Our analysis has as corpus texts of the genre sketches, specifically the comedy videos produced by the Porta dos Fundos Group. The choice for this corpus, besides the great success that these videos of comedy have made and to this day in the midst of the digital media, was due to the fact that they are relatively short texts, but that they present a complete linguistic interaction, not only as to the sequence of statements, but also in the context surrounding them, allowing a pragmatic analysis. After the theoretical presentation on the acts and the implicatures, a notion of the genre sketching and a description of the group Porta dos Fundos is also presented. At a later point, we address some theoretical foundations for a characterization of mood. Then, a survey, an analysis and a description of the speech acts and the implicatures identified in the selected sketches, object of this research, are made, allowing the verification of the pragmatic phenomena in the selected texts. We tried to verify: 1) the presence or not of a regularity among the data found; 2) the change of the expectation in relation to the chain of events; 3) the game of implicit; and 4) the relationship of constitutive components of humor with the sketches. For the established objectives, this research acquires a character of quantitative-qualitative character of descriptive approach with the objective of investigating the speech acts and the implicatures in the genre sketch.